The effects of forest patch size on bird biodiversity - Kadis, Nur Faizza (2018)
In Malaysia, forest fragmentation has become a great concern as it causes environmental degradation. Forest fragmentation occurs when original large and continuous forest is divided into small patches of forest. Forest fragmentation affects the forest fauna diversity. This study was conducted to investigate the species richness and abundance of the forest birds within four fragmented forests in Selangor. The four fragmented forest reserves were located within urban landscape, these study sites were Sungai Lalang Forest Reserve (SLFR), Ayer Hitam Forest Reserve (AHFR), Bukit Cerakah Forest Reserve (BCFR) and Bangi Forest Reserve (BFR). Point transect survey was used as a method for this study. Thirty sampling points were prepared for all study sites. One-way ANOVA was used to compare the abundance and richness of forest bird species among study sites. The BFR was recorded as the highest species richness compared to other sites. The highest bird abundance was recorded at AHFR compared to the other fragmented forests. This result is somewhat contradictory with previous studies which suggested large forest supports a high number of bird abundance and species richness. Similarity Percentage analysis (SIMPER) was used to determine the species composition within each forest patches. The contributions from this study were to update the biodiversity information within each forest patch and made a management recommendation for stakeholder to protect the biodiversity.